MENTAL HEALTH IMPLICATIONS OF COVID-19: A NARRATIVE REVIEW OF THE LITERATURE - Habib, Hina Ayaz; Habib, Nina Ayaz; Hussain, Shehzad; Mian Mukhtar -ul- Haq (Journal of Pakistan Psychiatric Society, 2022)
Introduction: The novel coronavirus disease, which the World Health Organization (WHO) officially designated as COVID-19, originated in Wuhan, China, as a cluster of unexplained pneumonia cases. It has affected countries worldwide and has been classified as a pandemic. To deal with this global health crisis and to curtail the spread of the virus, stringent public health measures have been implemented. There is evidence of a positive correlation between widespread outbreaks of contagious diseases, symptoms of psychiatric illness, and psychological distress. Aim: Considering the need to develop a deeper understanding of COVID-19 to devise strategies to deal with and prevent impact of COVID-19 on mental health thereby present review is undertaken. Method: A narrative review was conducted in May 2020. Result: Findings are suggestive that healthcare workers engaged in providing care to patients affected by COVID-19 are at a risk of developing psychological issues such as vicarious traumatization. With regards to the public, certain populations, including individuals with preexisting mental health issues, are more vulnerable to adverse psychological impacts from COVID-19. To conclude it, the review findings highlight the hidden mental health impact of COVID-19 and allows health care workers in all specialty to watch for vulnerable patients, their family members, and colleagues who may adversely psychologically affected by COVID-19.